Effects of basic amino acid on the tenderness, water binding capacity and texture of cooked marinated chicken breast. (July 2020) - Zhang, Yinyin; Zhang, Daojing; Huang, Yajun; Chen, Li; Bao, Pengqi; Fang, Hongmei; Xu, Baocai; Zhou, Cunliu
Abstract: This work investigated the effects of basic amino acids such as l -arginine (Arg)/l -lysine (Lys) on the physicochemical properties of cooked marinated chicken breast (CMCB) as well as the possible mechanism underlying these effects. The results indicated that shearing force decreased from 13.3 N to 10.0 N and cooking loss decreased from 38.3 g/100 g–26 g/100 g when Lys increased from 0 g/100 g–0.4 g/100 g, while shearing force decreased to 8.8 N and cooking loss decreased to 28 g/100 g at 0.4 g Arg/100 g. Furthermore, Arg/Lys improved the textural parameters and increased pH value. Low field-nuclear magnetic resonance showed that Arg shortened the relaxation times of T21 from 50 ms to 38 ms and Arg/Lys increased the peak area percentage (P21 ) for T21 from 93.6 to 97. Arg/Lys promoted the extraction of salt-soluble meat proteins from 54 mg/g to 78.6 mg/g. Scanning electron microscopy illustrated that Arg and Lys narrowed the gaps between muscle fibers at 0.6 g/100 g and at 0.4 g/100 g, respectively. The results disclosed that Arg/Lys could improve the physicochemical properties of CMCB, and thus showing a potential for the manufacture of cooked marinated meat products. Highlights: Arginine/Lysine were used for the manufacture of cooked marinated chicken breast. Arginine/Lysine reduced shearing force and cooking loss. Arginine/Lysine raised immobilized water fraction. Arginine/Lysine promoted the extraction of salt-soluble meat proteins. Arginine/Lysine narrowed the gaps between muscle fibers.